Does Transvaginal Ultrasound at 13–15 Weeks Improve Anatomic Survey Completion Rates in Obese Gravidas?. Issue 7 (July 2021) - Toscano, Marika; Grace, Daniel; Pressman, Eva K.; Thornburg, Loralei L.
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2021;34:803–809) The fetal anatomic survey is less likely to be completed or is completed at a later gestational age in pregnant women who are obese. This reduces the likelihood of detecting fetal anomalies at an earlier stage of pregnancy.